A self-cutting teenager. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
A self-destructive behavior, and in particular self-cutting the skin is not exceptional and typically begins in adolescence. A multicenter survey conducted on over 12,000 European teenagers (1) showed that 27.6% had carried out voluntarily the injuries, most occasionally, 7.8% on a repetitive basis. The lesions may be parallel or crossed, more or less deep cuts or drawings or inscriptions. The teenager who cuts does not make that to show others his/her injuries as happening in dermatitis artefacta. For this reason he/she does not choose sites exposed as the face and hands, but the most accessible sites that can be hidden, so mainly the limbs, particularly the wrists, forearms and arms prevalently on the non-dominant limb, thighs and legs. The lesions are then discovered by chance; on the other hand, the teenager who cuts him/herself publicly, in visible locations or that flaunts the injuries and continues to carry out them repetitively has a borderline personality or psychiatric disorders (2). The self-cutting teenager procures secretly the injuries not to attract the attention of others as in dermatitis artefacta, but as a remedy to a situation of psychological stress, resorting to physical pain to silence a stressful psychological situation, for example feelings that cause anxiety, anger, depression (2).